A Theory of Tax Avoidance - Managerial Incentives for Tax Planning in a Multi-Task Principal-Agent Model - Ralf Ewert; Rainer Niemann (Center for Economic Studies and ifo Institute (CESifo), 2014)
We derive determinants of tax avoidance by means of a multi-task principal-agent model. We extend prevailing models by integrating both corporate and individual income taxation as well as by including tax planning effort in the agent's action portfolio. Our model shows novel and apparently paradoxical results regarding the impact of increased tax rates on efforts, risks, and incentive schemes. First, the principal's after-tax profit can increase with a higher corporate tax rate. Second, tax planning effort can decrease in the corporate tax rate. Third, operational effort can increase with increasing corporate tax rates. We show that differences in productivities, differences in operational and tax risk and the correlations of these risks are crucial determinants for the optimal degree of tax avoidance. These determinants can explain why some firms are more tax aggressive than others and should therefore be considered in empirical studies. Related to this insight, we demonstrate that our results are consistent with recent empirical evidence.
Keywords: H24; H25; M41; 330; tax avoidance; principal-agent theory; tax planning; multi-task models; corporate governance